Experimental investigation of debris entrapment in annular contacts - Aleksejev, J; Clark, Z; Huber, J; Hills, DA (SAGE Publications, 2020)
In wearing contacts, a part of the wear debris is trapped between the surfaces, creating a wear debris bed. Many researchers report such beds providing a degree of protection against further wear. It was hypothesized, that in an annular contact, the level of debris entrapment increases with the width of the annulus resulting in decrease in wear. To test this hypothesis, two series of experiments using EN1A steel and 6082T6 aluminium alloy annuli, measuring 1, 2 and 4 mm wide were carried out. When steel was used, there was no clear correlation between ring width and total mass loss or steady state wear rate. When aluminium was used, wear decreased with the ring width according to both metrics. This behaviour appears to correlate with worn surface roughness, suggesting that the worn surface roughness to be a parameter controlling debris entrapment